The Database of Cartoons and Commercials as Visually-Oriented Language Input: Motivations, The Procedure and Methodological Issues - Pınar İbe Akcan; Umut Ufuk Demirhan (Dilbilim Araştırmaları Dergisi, 2016)
Cartoons and commercials on television may be important resources for the acquisition and learning processes of children in both linguistic and non-linguistic domains. However, there are not adequately many studies in the linguistics literature about them, particularly emphasizing their importance as a form of visually oriented language input in the language acquisition process. The aim of the current study is to introduce a database of cartoons and commercials in Turkish, presenting its major motivations, its construction procedure and some of the basic issues that were experienced during the construction process. The paper aims to make methodological contributions for further studies that have similar objectives.